Incarcerating First Nations Women in Australia: A Case for Intersectional Analysis - Megan Beatrice (2024)
First Nations women represent the fastest-growing population in the Australian prison system, with escalating rates of incarceration the subject of extensive inquiry. Nevertheless, the crisis persists. This paper argues that the unique situation of First Nations women within a colonial criminal justice system requires reframing and reimagining, in order to think differently about the crisis. One way this can be achieved is by taking an intersectional approach. Applying an intersectional lens to the crisis of over-incarceration of First Nations women identifies gender, race, and colonialism as intersecting points of disadvantage, the impact of which warrants further investigation. It is not suggested that these factors are the only intersecting points of disadvantage for First Nations women, but rather that they represent intersections common across the colonised jurisdictions, with common theoretical underpinnings. This article conducts a critical review of the existing literature, to expose space for an intersectional analysis of the problem, and offers an intersectional interpretation of the factors contributing to the over-incarceration of First Nations women.